Communities in Conflict: The Rivalry between the Cults of Sts. Anastasia and Chrysogonus in Medieval Zadar - Vedriš, Trpimir (2005)
The paper inquires the "struggle" between the two principal patron saints of Dalmatian city of Zadar between the twelfth and the fourteenth centuries. It points to some apsects of the town's history such as an unbroken tradition of urban living since Antiquity and the importance of the bishop in the Early Middle Ages, observing the development of the cult of early patron saint, St. Anastasia. When, with the emergence of the commune and fragmentation of the spiritual and secular authority, the urban monastery of St. Chrysogonus came to play a major political role (its abbots opposing the authority of the archbishops of Zadar and actively participating in the resistance to Venice) the political tensions found their expression in devotion to the patron saints of the communities in conflict. While the cult of St. Anastasia, venerated in the city cathedral, was more important in the early Middle Ages, the cult St. Chrysogonus came to play an important role in city politics only with the growing power of the monastery in the High Middle Ages. Venerated in the early period as a monk, Chrysogonus came to be represented as a knight, whose image as a charging horseman came to symbolise the pride and self-confidence of the commune of Zadar. With the upgrading of the bishopric to the archbishopric level in the mid-twelfth century the position came under the strong influence of the Venice, leading eventually to the introduction of "Venetian" bishops in the following centuries. At the same time, the monastery developed strong relations with the Croatian and Hungarian court, becoming the political power known as the "king's party" in Zadar. The paper shows how the cults of St. Anastasia and of St. Chrysogonus reflected these tensions, and how the social and political circumstances led to the replacement of the city's principal patron saint St. Anastasia, and established St. Chrysogonus as the new principal patron of the commune.
Projekt MZOS
ENG